The home bias in sovereign ratings - Fuchs, Andreas; Gehring, Kai (Discussion papers, 2015)
Credit rating agencies are frequently criticized for producing biased sovereign ratings. This article discusses how the home country of rating agencies could affect rating decisions as a result of political economy influences and cultural distance. Using data from nine agencies based in six countries, we test whether agencies assign better ratings to their home countries, as well as to countries economically, geopolitically and culturally aligned with them. Our results show biases in favor of the respective home country, culturally more similar countries, and countries in which home-country banks have a larger risk exposure. Linguistic similarity seems to be the main transmission channel that explains the advantage of the home country.